The walkability of Alvalade neighbourhood for young people: An agent-based model of daily commutes to school - Sampayo, M. T. de.; Sousa-Rodrigues, D. (Proceedings of the 6th International Conference of Contemporary Affairs in Architecture and Urbanism (ICCAUA2023), 2023)
The Alvalade neighbourhood in Lisbon, Portugal, was built in the mid-XX century as low-cost housing for workers, but it has become inhabited by the middle and upper classes. The neighbourhood is home to a large population of young people, including children and teenagers who attend the schools located in the area. We present an agent- based model which aims to investigate the walkability of the neighbourhood for these young people, focusing on the mobility patterns of children and teenagers as they navigate their daily routines of going to school. We simulate the pedestrian movement of these young people, considering factors such as the availability of sidewalks, crosswalks, distance to schools, and the presence of other amenities. Our research reveals the mobility patterns emerging in this area and compares them across the different schools in the area. These results inform both urban policies and interventions that promote safe and accessible routes to school.